Vocational rehabilitation service usage and outcomes for transition-age youth with serious mental health conditions. - Davis, Maryann; Koroloff, Nancy; Foley, Susan M.; Marrone, Joe; Kwan, Ngai (Journal of Vocational Rehabilitation, 2024)
BACKGROUND: The postsecondary vocational outcomes of students with mental health disabilities (MHD) are poor and vocational rehabilitation factors contributing to better outcomes have not been identified. OBJECTIVE: Characterize demographic, service use and service outcome differences between youth with MHD and youth with other disabilities from state vocational rehabilitation agencies (SVRA) and identify factors predicting service use and service outcomes within youth with MHD. METHODS: Data were from 2015–2017 Rehabilitation Services Administration-911 case closure files. The sample consisted of 14–24-year-old SVRA applicants. Cross-disability characteristics, service use and outcomes were compared. Within youth with MHD, multivariate analyses examined factors contributing to having an Individual Plan for Employment (IPE) and successful case closure (i.e., with employment). RESULTS: Youth with MHD were underrepresented, older at application and were less likely to have IPEs and successful closures than youth in other disability groups. Within youth with MHD, application age and SVRA characteristics were the strongest predictors of having an IPE. Education and employment status at application strongly predicted successful closure. CONCLUSION: Youth with MHD, as in previous cohorts, continue to have lower service use and successful SVRA outcomes. Efforts are needed to increase their connection to SVRAs at younger ages. Youth with MHD without employment at application may need additional supports to achieve successful closures. Addressing several SVRA performance characteristics may improve their service use and outcomes.